Article review "Ethical issues of xenotransplantation in the aspect of religious views" the authors R .A. Sharifova, A. Kh. Breizat, M. M. Kaabak, U. V. Maslikova, B. I. Yaremin - E. V. Bryzgalina; N. N. Rappoport; E. I. Babenko (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2022)
.